Expert Opinions on Best Practices for Overactive Bladder Management with onabotulinumtoxinA - Karyn S. Eilber; Benjamin M. Brucker; Andrea Pezzella; Vincent Lucente; Kevin Benson; Michael J. Kennelly (Toxins)
OnabotulinumtoxinA is an FDA-approved treatment for adults with overactive bladder (OAB) who have an inadequate response to, or are intolerant of, oral pharmacotherapies including anticholinergics or beta-3 agonists. However, procedural practices of onabotulinumtoxinA intradetrusor injection vary among practitioners and can affect patient experience. To address this, a panel of six high-volume intravesical onabotulinumtoxinA providers with 100 years of combined experience convened to discuss the best office practices when treating patients with OAB. These key best practices include counseling patients on available OAB therapies, including onabotulinumtoxinA, at the initial consultation in accordance with established AUA and SUFU guidelines in a way that is easily understood. An office setting is preferred over a hospital or surgery center when performing the procedure. Staff involvement, from scheduling to post-procedure, is essential for establishing the relationships necessary to optimize patient experience and encourage compliance and retreatment. Experts generally recommend using a viscous lidocaine bladder instillation for an anesthetic 15 min prior to the reconstitution of onabotulinumtoxinA with 5 to 10 mL of normal saline. A range of one to 20 injection sites is acceptable, with a smaller number preferred. Starting in the lower bladder, experts recommend using a slower speed of injection to improve distribution and decrease patient discomfort. Subsequent treatments should be regularly scheduled at six-month intervals with the option of re-treating earlier if symptoms return, but no sooner than 12 weeks. For office intravesical onabotulinumtoxinA procedures, optimization of the patient experience by the physician and their staff, starting with the initial visit through the post-treatment follow-up, is key to long-term patient compliance.